Integrated Online Access to Objects and Archives - Niu, Jinfang (Archivaria, 2018)
In this study, 100 museums were randomly selected from the 4,184 members of the American Alliance of Museums. The websites of sampled museums were examined to identify the approaches used to provide integrated online access to objects and archives. It was found that many museums either made no mention of their collections on their websites or provided online access to either objects or archives but not to both. Some museums that allowed online access to both objects and archives did not integrate the access to the two types of collections. Only a small percentage of museums provided integrated online access to objects and archives. From these museums, five different approaches for integrated online access to objects and archives were identified. The findings show that museums in the United States are still in the early stages of providing integrated online access to disparate collections. However, integrated online access to disparate collections is likely to become more common in the future due to the merits of online access and the convergence of libraries, archives, and museums. RÉSUMÉ Pour cette étude, nous avons choisi au hasard cent musées parmi les 4,184 membres de la American Alliance of Museums. Nous avons examiné les sites web des musées sélectionnés afin d’identifier les approches utilisées pour donner accès à leurs objets et à leurs archives en ligne de façon intégrée. Nous avons constaté que plusieurs musées ne font aucune mention de leurs collections sur leurs sites web, ou encore ne donnent accès qu’aux objets ou aux archives, mais pas aux deux. Certains musées qui donnent un accès tant aux objets qu’aux archives n’ont toutefois pas intégré les deux types. Seul un petit pourcentage des musées offre un accès en ligne aux objets et aux archives intégrés. De ces musées, cinq différentes approches à un accès intégré aux objets et aux archives en ligne ont été identifiées. Ces résultats révèlent que les musées aux États-Unis en sont toujours aux premières étapes visant à permettre un accès en ligne à leurs collections disparates de façon intégrée. Cependant, l’accès intégré en ligne aux collections disparates sera probablement plus fréquent à l’avenir étant donné les avantages de l’accès en ligne et la convergence des bibliothèques, des archives et des musées.